It's not about the leaders: It's about the practice of leadership - Joseph A. Raelin (Organizational Dynamics, 2016)
This article explores the mythology of leadership as residing in particular individuals. It argues that given the complex requirements of 21st Century management, we can no longer allow the rest of the organization, other than its managers, to sit idly awaiting orders from detached bosses. It looks at leadership, consequently, not as manifestly being about individual leaders, but about the collective interactive practices that accomplish the choices we make together in our mutual work. After deriving the grounds for our myopic charismatic approach to leadership, it calls for a transition to a leadership-as-practice, and names some of the vital activities associated with this approach. Undergirding them is the essential practice of dialogue in which through dedicated listening, new ideas can be generated never thought of prior to the dialogue. The article also illustrates the sustainable benefits of the practice approach and shows how leadership development needs to be altered to take advantage of learners' active collective engagement within the work setting. Action learning with reflective dialogue is viewed as a superior alternative to classic competency training. By the end, readers might appreciate that leadership can be usefully shared among those doing the work.
Keywords: J24; M10; M12; M14; M53; M54; 330; leadership; leadership development; leadership-as-practice; collective leadership; dialogue; action learning